How EFL Instructors Improve Their Professionalism: The Voice from Indonesian Higher Education Institutions - Qamariah, Hijjatul; Hercz, Maria (SCAD Independent, 2025)
Professional development in Indonesia has been widely researched, with much of the focus on secondary school teachers. Some studies have explored professional development among tertiary education teachers, but research on the professional development of English as a Foreign Language (EFL) instructors in higher education in Indonesia remains limited. This gap is significant, given the crucial role of EFL instructors in preparing future English teachers, which demands exceptional professionalism. This research aimed to explore the factors contributing to the professional development of EFL instructors in higher education in Indonesia. The data for this study were collected through semi-structured interviews with ten EFL instructors (five female and five male) from various universities in Indonesia. The interview questions covered topics such as their views on professional development, efforts to improve themselves, participation in professional development programs and activities, personal initiatives, and institutional support. Each interview lasted between 35 and 45 minutes. The data were analyzed using the MAXQDA tool to identify themes from the interview transcripts. The findings revealed several key themes: (1) efforts for PD (2) EFL instructor beliefs (3) EFL instructors’ efficacy (4) Less institution support, (5) commitment to the job, (5) classroom practice. The study suggests that institutional support for EFL instructors should be enhanced. Professional development programs should be consistently provided and maintained to ensure their effectiveness and sustainability.